Transcriptomics and metabolomics together reveal the underlying mechanism of heroin hepatotoxicity. (1st January 2023) - Yue, Yingbiao; Zou, Lei; Tao, Jie; Yin, Lin; Xie, Zhenrong; Xia, Yu; Zhang, Zunyue; Wang, Kunhua; Zhu, Mei
Abstract: Researches on heroin are more about addiction and some infectious diseases it causes, but liver fibrosis caused by heroin abuse and the mechanism of heroin hepatotoxicity in addicts are ignored. To explore the mechanism of heroin hepatotoxicity, mice in heroin group were intraperitoneally injected by heroin (10 mg/kg) once a day for 14 consecutive days, while mice in heroin withdraw group underwent another 7 days without heroin administration after the same treatment as heroin group. The levels of alanine aminotransferase （ALT）and aspartate aminotransferase （AST） in serum, as biochemical indexes, were applied to evaluate liver damage. H & E staining and oil red O staining were used to observe the pathological changes of liver. Transcriptomics and metabolomics were applied to detect genes and metabolites in livers. The results of biochemical analysis and pathological examination showed that heroin induced liver damage and lipid loss in mice, and these mice did not return to normal completely after a short-term withdrawal. A total of 511 differential genes and 78 differential metabolites were identified by transcriptomics and metabolomics. These differential genes and metabolites were significantly enriched in pathways like lipid metabolism, arachidonic acid metabolism, glutathione metabolism, TCA cycle. And after undergoing 7-day withdrawal of heroin, most of the above differential genes and metabolites did not return to normal. Our study revealed the hepatotoxicity of heroin and that short-term withdrawal of heroin did not fully restore liver function. In addition, transcriptomics and metabolomics revealed that lipid metabolism and arachidonic acid metabolism may be potential therapeutic targets of heroin hepatotoxicity, providing a basis for the treatment of heroin addiction patients in the future.